Monitoring, modelling and managing beaver (Castor fiber) populations in the River Otter catchment, Great Britain. Issue 3 (3rd August 2022) - Graham, Hugh A.; Puttock, Alan; Chant, Jake; Elliott, Mark; Campbell‐Palmer, Roisin; Anderson, Karen; Brazier, Richard E.
Abstract: Eurasian beaver ( Castor fiber ) were nearly hunted to extinction but have recovered to occupy much of their former range. Beaver were extirpated from Great Britain c. 400 years ago but have recently been reintroduced. The River Otter catchment, Devon was the site of the first licensed wild release of beavers in England. With further releases being considered, there is a need to better understand population dynamics of this native, keystone species to inform conservation and management. Field signs were surveyed from 2015 to 2021. A semi‐automated territory detection method was adopted to estimate territory counts. A spatially explicit model was developed to estimate the ecological territory capacity of the catchment. Future territory expansion was modelled using logistic growth curves; initial growth rate was estimated from observed territory counts and the estimated territory capacity range was used to define the limiting value of the growth curve. Beaver territory removal was simulated, across a range of management intensities and start times, to determine potential impacts of translocation or lethal control upon population dynamics. Territory numbers increased from four to 18, inclusive of four additionally released individuals, during study period. In the absence of population management, the territory capacity of the catchment was estimated to range between 120 and 183; this may be reached between 2028 and 2057. Simulated territory removal, where territories were removed at a fixed rate from the sum of the estimated total population and the population increase for that year, demonstrated large uncertainties in predicted population responses. Simulations with territory removals >3/year all predicted potential population collapse. This finding emphasizes the need for caution when considering population management strategies; translocation of animals out of the catchment or culling should be considered only when populations are established and all alternatives have been considered. These results provide critical information for the expected rate and magnitude of beaver population change in the River Otter catchment. The methods provide a reproducible and generalizable approach for understanding beaver population change, which can inform policy on the reintroduction of beavers and the potential timing and intensity of future beaver population management. Abstract : Beaver field signs were surveyed annually in the River Otter Catchment, England to map the distribution of beaver activity between 2015 and 2021. These data were used to estimate the territory expansion rate over the period which was then used to inform predictive models for future population change. A range of territory removal simulations were tested to predict the impact of potential future management strategies showing significant uncertainty in projected responses to population control.